Spaces of Resistance: Heterotopia and Dystopia in Toni Morrison’s Home - Gonçalves, Alice Ferreira Magalhães (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
The following paper aims to show that Toni Morrison’s Home (2012) can be read and analyzed as a novel in which the spaces of black people in American society can be seen as both heterotopic and dystopian according to spatiality studies. The objective of this essay is to prove that it would be accurate to apply those concepts by developing an argument that focuses on how the spaces of the mind, of the body and the physical spaces affect the course of the novel and its characters, as well as the way in which the relationship between these spaces is meaningful to that reading. It is important to offer this reading of the novel, not only because the social dimension of the racial conflict in the USA is still very intense, but also because it provides a point of view that is relevant for social and cultural studies. At the end of the article, it can be noticed that a close reading of the novel applying the concepts of heterotopia – developed by Foucault in the 1960s and published 20 years later -, dystopia and spatiality studies enriches its analysis and interpretation, by offering alternatives to the more common and mainstream approaches to this work.